How Economic Conditions of a Country Impact its Local Tourism - Verde; Lopes da Costa, R.; Gonçalves, R. (VI International Forum on Management – Familia y tecnología: Factores de resiliencia de las PYMEs durante la pandemia, 2022)
Tourism has been getting worldwide attention due to being a catalyst for economic growth. While some authors defend that the consequences brought by an economy reliant on tourism overshadow its benefits, the opinions get split over the reliability of tourism as a main contributor to economic development. There is a huge gap in the literature when it comes to the social, cultural, and environmental impacts of tourism development mostly due to being an issue neglected by governments and private entities. This investigation will provide us new information on the topic and a more accurate view on the upsides and downsides of tourism for the locals. Using data provided by the government it was made a correlative analysis in order to identify trends and correlations. In this study it is shown that innovations have a positive contribution for tourism growth even though these face many threats in the process, like customer resistance. This investigation concludes that tourism cannot be seen as a panacea due to the risks associated with it but, if properly managed, can be an asset like nearly no other industry. It is undeniable the dire importance of innovations and entrepreneurs in boosting the competitiveness and attractiveness of the industry, but the final note is that these have limited impacts as the real influence lies on the government and its laws which, in some scenarios, particularly in India, is more often a liability rather than a reliability.